Are neutrophil extracellular traps the link for the cross-talk between periodontitis and rheumatoid arthritis physiopathology?. (22nd March 2021) - Oliveira, Sicília Rezende; de Arruda, José Alcides Almeida; Schneider, Ayda Henriques; Carvalho, Valessa Florindo; Machado, Caio Cavalcante; Corrêa, Jôice Dias; Moura, Marcela Faria; Duffles, Letícia Fernanda; de Souza, Flávio Falcão Lima; Ferreira, Gilda Aparecida; Costa, Fernando Oliveira; Abreu, Lucas Guimarães; et al.
Abstract: Objectives: Neutrophil extracellular traps (NETs) play a role in the pathogenesis of periodontitis and rheumatoid arthritis (RA). However, it remains poorly understood whether NETs participate in the cross-talk between periodontitis and RA. Herein, we investigated the production of NETs in individuals with periodontitis and RA and its association with clinical parameters. The impact of periodontal therapy on RA and NET release was also assessed. Methods: The concentration of NETs and cytokines was determined in the saliva and plasma of individuals with early RA ( n = 24), established RA ( n = 64) and individuals without RA ( n = 76). The influence of periodontitis on the production of NETs and cytokines was also evaluated. Results: Individuals with early RA had a higher concentration of NETs in saliva and plasma than individuals with established RA or without RA. Periodontitis resulted in an increase in the concentration of NETs of groups of individuals without RA and with early RA. The proportion of individuals with high concentrations of IL-6, IL-10 and GM-CSF was higher among individuals with periodontitis than among individuals without periodontitis. The concentrations of TNF-α, IL-6, IL-17/IL-25 and IL-28A were particularly high in individuals with early RA. Worse periodontal clinical parameters, RA onset and RA activity were significantly associated with circulating NETs. Periodontal therapy was associated with a reduction in the concentration of NETs and inflammatory cytokines and amelioration in periodontitis and RA. Conclusion: This study reveals that NETs are a possible link between periodontitis and RA, with periodontal therapy resulting in a dramatic switch in circulating NET levels.